Physalin D regulates macrophage M1/M2 polarization via the STAT1/6 pathway. Issue 6 (14th October 2018) - Ding, Ning; Wang, Yuxing; Dou, Ce; Liu, Feila; Guan, Ge; Wei, Keyu; Yang, Jingyuan; Yang, Mingcan; Tan, Ju; Zeng, Wen; Zhu, Chuhong
Abstract: The in vitro and in vivo effects of physalin D on macrophage M1/M2 polarization were investigated. In silico analysis was first performed for biological function prediction of different physalins. The results suggest physalins have similar predicted biological functions due to their similarities in chemical structures. The cytotoxicity of physalins was then analyzed based on cell apoptosis rate and cell viability evaluation. Physalin D was chosen for further study due to its minimal cytotoxicity. Bone marrow macrophages were isolated and induced with lipopolysaccharide/interferon (IFN)‐γ for M1 polarization and interleukin (IL)‐4/IL‐13 for M2 polarization. The results showed that physalin D can repolarize M1 phenotype cells toward M2 phenotype. In addition, physalin D is protective in M2 macrophages to maintain the M2 phenotype in the presence of IFN‐γ. On the molecular level, we found that physalin D suppressed the signal transducers and activators of transcription (STAT)1 activation and blocked STAT1 nuclear translocation. Conversely, physalin D can also activate STAT6 and enhance STAT6 nuclear translocation for M2 polarization. Taken together, these results suggested that physalin D regulates macrophage M1/M2 polarization via the STAT1/6 pathway. Abstract : Physalin D suppressed signal transducers and activators of transcription (STAT)1 activation and blocked STAT1 nuclear translocation. Conversely, physalin D can also activate STAT6 and enhance STAT6 nuclear translocation for M2 polarization. Taken together, physalin D regulates macrophage M1/M2 polarization via the STAT1/6 pathway.